Dynamic Effects of Crude Oil Price Volatility on Manufacturing Output and Industrial Performance in Nigeria (1994-2024) - Gelle Dungrit Peter; Toryila Raphael Orshio (Integrated Economies and Policy Insights, 2025)
This study examines the impact of crude oil price fluctuations and manufacturing output in Nigeria between 1994 and 2024. Employing the Autoregressive Distributed Lag (ARDL) technique, the research investigates the relationship among manufacturing output (lnMANOUT), crude oil price fluctuations (COPF), exchange rate (EXR), and population labour force (PLF). The Augmented Dickey-Fuller (ADF) test confirmed that the variables were stationary at levels I(0) or first difference I(1). The ARDL bounds test revealed the existence of a long-run co-integrating relationship, while the Error Correction Model (ECM) confirmed a negative and statistically significant adjustment back to equilibrium despite short-run fluctuations. The findings indicate that crude oil price fluctuations exert a positive and statistically significant effect on manufacturing output, suggesting that oil windfalls can stimulate industrial activity through higher revenues and investment. Conversely, exchange rate volatility displayed a negative and statistically significant impact, reflecting depreciation-induced increases in the cost of imported machinery and inputs. The population labour force had a positive and significant influence on manufacturing output, underscoring the role of productive labour in driving industrial performance. Additionally, the Pairwise Granger Causality test revealed a Bidirectional causality running from crude oil price to manufacturing output, emphasizing the sector’s sensitivity to global oil market dynamics. The study concludes that oil prices, exchange rate stability, and labour dynamics are key determinants of manufacturing output in Nigeria. It recommends coordinated monetary–fiscal actions to stabilize the exchange rate; channeling oil revenues into reliable energy, transport infrastructure, and domestic raw-material development; and reducing import dependence through backward integration, local sourcing, well-governed industrial zones, and workforce upskilling.